2008
DOI: 10.3354/meps07212
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized anthesis and predation on pollen in the marine angiosperm Thalassia testudinum (Hydrocharitaceae)

Abstract: Synchrony in the anthesis of male and female flowers of the hydrophilous dioecious marine angiosperm Thalassia testudinum was studied by following flower buds of 64 staminate and 34 carpellate flowers in situ during night and day to observe the timing of flower opening. Anthesis of female flowers occurred throughout the day, with a slight peak between 15:00 and 17:00 h. The time lapse between initiation of anthesis and full opening of the flowers was ∼2 to 3 h. Anthesis in male flowers was highly synchronized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Morphological features such as highly reduced floral structures, filamentous pollen, elongated stigmas or the prevalence of dicliny are considered to be adaptations to the transport and interception of pollen in the aquatic medium (see Ackerman 2006 for summary). However, there are other traits of the hydrophilous syndrome that are better explained as a response to pollen dilution, such as copious pollen production and mechanisms of pollen concentration, for example pollen release in mucilaginous masses or strands (Ackerman 2006), restricted flowering periods (Inglis & Lincoln Smith 1998, Walker et al 2001, Van Tussenbroek et al 2009) or synchronized pollen release (Van Tussenbroek et al 2008, 2009). Thus, pollen limitation could have been an important selective agent in the evolution of the life history characteristics for this ecological group of marine angiosperms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphological features such as highly reduced floral structures, filamentous pollen, elongated stigmas or the prevalence of dicliny are considered to be adaptations to the transport and interception of pollen in the aquatic medium (see Ackerman 2006 for summary). However, there are other traits of the hydrophilous syndrome that are better explained as a response to pollen dilution, such as copious pollen production and mechanisms of pollen concentration, for example pollen release in mucilaginous masses or strands (Ackerman 2006), restricted flowering periods (Inglis & Lincoln Smith 1998, Walker et al 2001, Van Tussenbroek et al 2009) or synchronized pollen release (Van Tussenbroek et al 2008, 2009). Thus, pollen limitation could have been an important selective agent in the evolution of the life history characteristics for this ecological group of marine angiosperms.…”
Section: Discussionmentioning
confidence: 99%
“…The same set of male flowers was used for ~10 female flowers; previous trials in the laboratory showed that this procedure resulted in ample pollen supply to the stigmas. The stigmas were receptive immediately after opening of the female flowers (Van Tussenbroek et al 2009), and they were pollinated in the evening because the male flowers dehisce at dusk (Van Tussenbroek et al 2008) and pollen grains were short-lived (only 50 to 60% of the pollen grains were viable after 13 h, Van Tussenbroek et al 2009). The following day, 40 additional recently opened female flowers were marked as controls (CP: control, no pollen addition) in the same plot.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty of such shoots were measured to characterize their morphology and evaluate their differences with shoots of quantitative samples collected far from the edge of the P. oceanica bed Piazzi et al, 2005;Van Tussenbroek et al, 2008. All collected shoots were washed from the sediments and fixed in 4% formalin. For each sample the presence of male flowers was noted and the flowering percentage (no.…”
Section: Study Sitementioning
confidence: 99%
“…At the onset of night-time, mature male flowers initiate dehiscence, and pollen grains, embedded in a mucilaginous matrix, are released within 1 to 2 h (Van Tussenbroek et al 2008, 2009. The synchronized nocturnal flowering may aid to avoid pollen predation by diurnally active parrotfish or may serve to synchronize male and female functions (Van Tussenbroek et al 2008, 2009. However, at dark, the abundance of smaller fauna in the seagrass canopy increases (Heck & Orth 1980, Bauer 1985, Howard 1987.…”
Section: Introductionmentioning
confidence: 99%